EFEKTIVITAS MODEL PEMBELAJARAN COOPERATIVE TIPE THINK TALK WRITE TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA PADA PELAJARAN EKONOMI - hanifah, Hanifah; Sumarno, Sumarno; Rizka, Mifta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the Cooperative Learning model of the Think Talk Write type in improving students’ critical thinking skills. The study employed a quantitative approach with an experimental design. The research population consisted of 152 tenth-grade students, with a sample of 37 students from class X.1 selected as the experimental group. Data were collected through pretest and posttest instruments to measure students’ critical thinking skills, as well as observation sheets to assess learning activities. The collected data were analyzed using a Paired Sample T-Test to examine differences in students’ critical thinking skills before and after the implementation of the learning model, and an N-Gain test to determine the level of improvement. The results indicate that the implementation of the Cooperative Learning Think Talk Write model significantly improved students’ critical thinking skills, as evidenced by a Sig. (2-tailed) value of < 0.05 that is ,000 and an N-Gain score of 0.7910, which falls into the moderate category. Therefore, it can be concluded that the Think Talk Write learning model is effective in enhancing students’ critical thinking skills in Economics learning.